If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (15x + 5)(10x + 25) = 0 Reorder the terms: (5 + 15x)(10x + 25) = 0 Reorder the terms: (5 + 15x)(25 + 10x) = 0 Multiply (5 + 15x) * (25 + 10x) (5(25 + 10x) + 15x * (25 + 10x)) = 0 ((25 * 5 + 10x * 5) + 15x * (25 + 10x)) = 0 ((125 + 50x) + 15x * (25 + 10x)) = 0 (125 + 50x + (25 * 15x + 10x * 15x)) = 0 (125 + 50x + (375x + 150x2)) = 0 Combine like terms: 50x + 375x = 425x (125 + 425x + 150x2) = 0 Solving 125 + 425x + 150x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '25'. 25(5 + 17x + 6x2) = 0 Factor a trinomial. 25((5 + 2x)(1 + 3x)) = 0 Ignore the factor 25.Subproblem 1
Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5Subproblem 2
Set the factor '(1 + 3x)' equal to zero and attempt to solve: Simplifying 1 + 3x = 0 Solving 1 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 0 + -1 3x = 0 + -1 Combine like terms: 0 + -1 = -1 3x = -1 Divide each side by '3'. x = -0.3333333333 Simplifying x = -0.3333333333Solution
x = {-2.5, -0.3333333333}
| 2b+2=4 | | 0.1x=56 | | x+8+2y+5=180 | | 12.9=x+71 | | 2.74=2y | | PQ=QS | | 2z=2.4+0.2 | | 2w+5=-1 | | 2x-.5=.5x-4 | | -2(t-5)+8t=4t-6 | | -8x=14.3 | | 40=14y-4 | | -25x^2+9=o | | -3x-72=96-9x | | r-8=-32 | | W=0.3d-0.56 | | -104+3x=10x+50 | | 4(7m-1)+3(2-5m)=4(3m+5)-6 | | 0.3+5-3+0.1x=0.2(x-6) | | -201+12x=51-6x | | .20x+3y+3=2x-14y | | 14x-(5x+6)+16=4x | | 9-4x=17+4x | | 7x+9=9x+7 | | b=8m+9 | | 8x=26+14y | | 18-2x+x=6x-3 | | 90+45w=960 | | -132+2x=-6x+44 | | (x+2)-4=-3x+12 | | 4w+7x-13y+5w+5x+7y= | | 4y-2(4)=16 |